Fairness and the arm's length principle in a digital economy - Stefan Greil; Christian Schwarz; Stefan Stein (Hochschule Düsseldorf, Fachbereich Wirtschaftswissenschaften, 2018)
The OECD Base Erosion Profit Shifting (BEPS) Initiative as well as the current fairness oriented public discussion regarding the taxation of digital business models highlight the importance and complexity of the arm's length principle. In a theoretical model of an internationally fragmented digital good's production process, we show that fairness considerations of tax authorities (namely inequity aversion) can result in a falling apart between a perceived "fair" and arm's length distribution of profits across tax jurisdictions. Our model predicts that a multinational firm follows the fundamental paradigm of international taxation, i.e. the arm's length principle, to properly incentivize internal agents involved in the production of a digital good. However, with inequity averse tax authorities, we find that tax authorities "prefer" a more equal distribution of profits compared to the arm's length profit allocation. From a multinational firm's perspective, inequity aversion among tax authorities dampens the strategic effect to - in accordance with arm's length principle - shift profits to low tax countries. – – Die OECD Base Erosion Profit Shifting (BEPS) Initiative sowie die aktuelle Fairness orientierte öffentliche Diskussion zur Besteuerung digitaler Geschäftsmodelle verdeutlichen die Bedeutung und Komplexität des Fremdvergleichsgrundsatzes. Wir modellieren einen international fragmentierten Produktionsprozess eines digitalen Gutes und zeigen wie Fairness-Erwägungen von Steuerbehörden (d.h. Ungleichheitsaversion) dazu führen kann, dass die als "fair" wahrgenommene und die zum Fremdvergleichsgrundsatz konforme Gewinnverteilung innerhalb der Steuerjurisdiktionen auseinander fällt. Unser Modell sagt voraus, dass eines multinationales Unternehmen dem fundamentalen Paradigma der internationalen Besteuerung, d.h. dem Fremdvergleichsgrundsatz folgt, um firmenintern effiziente Anreize zur Produktion des digitalen Gutes zu setzen. Ungleichheitsaversion auf Seiten der Steuerbehörden führt allerdings dazu, dass die Steuerbehörden eine gleichmäßigere Verteilung der Gewinne im Vergleich zum Fremdvergleichsgrundsatz bevorzugen. Aus Sicht eines multinationalen Unternehmens dämpft die Ungleichheitsaversion der Steuerbehörden den strategischen Anreiz Gewinne in Niedrigsteuerländer zu verlagern.
urn:nbn:de:hbz:due62-opus-12029
Keywords: H26; H25; F23; 650; corporate income tax; profit-shifting; arm's length principle; fairness